A Realistic Approach to Calculating the Nitrogen Use Efficiency Index in Cereals with Winter Wheat (Triticum aestivum L.) as an Example - Witold Grzebisz; Jarosław Potarzycki (Agronomy)
Nitrogen use efficiency (NUE) is a reliable index of nitrogen (N) management, given that it expresses the real relationships that exist between crop yield, its components, and the content of available N (Nmin) in the soil in the critical stages of yield formation. This article proposes a method for calculating NUE which is based on N input (Nin) into the soil/crop system in the critical phases of yield formation in winter wheat. For the validation of this hypothesis, a field experiment with WW in three subsequent growing seasons (2012/2013, 2013/2014, 2014/2015) was used. Treatments were arranged in a factorial distribution of two factors: (1) three rates of soil-applied magnesium (Mgs, 0, 25, 50 kg Mg ha−1); (2) foliar application of Mg to winter wheat (no application—control; double-stage Mg application in BBCH 30 and in 49/50). The dose of N fertilizer (Nf) was 190 kg ha−1. Two groups of N pools (soil Nmin and N mass in the wheat biomass) were determined in BBCH 30, 58, and 89. These core datasets were used to calculate total N input (Nin) to the soil/crop system during the two main periods of WW growth: (1) before (vegetative mega-phase, V) and (2) after wheat flowering (reproductive mega-phase, R, or grain filling period, GFP). The number of grains per ear (GE) and the number of grains per unit area (grain density: GD) depended significantly on Nin at the onset of flowering. A Nin58 of 517 kg N ha−1 resulted in a GD of 28.3 × 1000 grains m−2, producing 9.47 t grain ha−1. The NUE indices calculated in the V phase were the best predictors of GE and GY. The apparently low NUE index in this phase clearly indicates (i) the high potential of winter wheat for grain set per ear, (ii) consequently resulting in a strong depletion of N soil resources during the GFP. Therefore, the reduced NUE before winter wheat flowering is essential for the achievement of a high GD. The NUE feedback phenomenon as found in this study is a crucial condition for the effective depletion of the inorganic N pool during the grain filling period of winter wheat. It can be concluded that the NUE indices obtained in the V mega-phase actually describe the N economy in winter wheat production very well.